Diabetes insipidus secondary to sarcoidosis presenting with caseating granuloma. (3rd March 2011) - Alam, Taimour; Thomas, Steven
Abstract : Diabetes insipidus is a rare complication of sarcoid infiltration of the hypothalamic-pituitary region. Non-caseating granuloma formation is typical of sarcoidosis. Anterior and posterior pituitary function may be affected. MRI coupled with endocrinology assessment is the usual method of investigation. A 25-year-old Caucasian male with no significant medical history presented with polyuria and polydipsia. Water deprivation test confirmed diabetes insipidus. CT scanning of the chest confirmed lymphadenopathy. Lymph node biopsy revealed caseating granuloma. Extensive investigation for tuberculosis was negative. The patient was started on intranasal desmopressin and steroids with marked improvement in symptoms. This is the first reported case of neurosarcoidosis with diabetes insipidus and caseation on histology that we are aware of. Differentiating between caseation due to sarcoidosis and tuberculosis on histology is possible by the use of special stains. Return of normal endocrine function is unusual and the patient is likely to require desmopressin therapy for life.